International Cooperation of Library and Information Institutions in the Republic of Uzbekistan - I. K. Tsai (Библиосфера, 2022)
Globalization is closely connected with the process of transition to a common information space. Libraries take an active part in this process. They, thanks to the development of cooperation, can use international experience, evaluate their activities and achievements, identify problems, improve the professional level of library specialists and participate in the development of new concepts for the development of library and information business and culture in general, intensify interaction with state and interstate coordination bodies. The article summarizes the experience of organization of work on the development of international cooperation between the libraries of the Republic of Uzbekistan with libraries and leading information, educational and scientific institutions, publishing houses of foreign countries, diplomatic missions, funds, representative offices of international organizations. It includes international document exchange, readers service within the framework of international interlibrary loan; project activities, preparation and holding of international scientific and practical conferences, symposiums, seminars, exhibitions, etc. The main directions of international activities of the National Library of the Republic of Uzbekistan named after A. Navoi and information resource centers of universities are also described. The author comes to the conclusion that for a fruitful solution of problems, it is necessary to create a legal framework, attract grant funds and organize joint commercial international projects.